Realitas Adati Hula-Hulaa to Syara’i, Syara’i Hula-Hulaa to Qur’ani - Mashadi Mashadi (Al-Ulum, 2012)
Islam has become the support and reference among Gorontalo people from the early period the religion. It is including in their way of life and daily activity such as daily lives and traditions. Therefore, it can be understood that Gorontalo is known with the philosophical "Adati hula-hulaa to saraa, saraa hula-hulaa to Kur'ani" which meant as "custom is based on the shari’ah, and so, the shari’ah is based on the Qur’an". This local value ​​is a philosophy of life that had been formulated from the Gorontalo first Muslim king, Sultan Amai. This concept was modified three times until the King Eyato with the concept as we know it today. Gorontalonese local wisdom as inferred in indigenous of "custom is based on the shari’ah, and so, the shari’ah is based on the Qur’an" uniquetly influence their way of lives and in the forms and implementation of religious values in Gorontalo.